Androgen receptor-independent prostate cancer: an emerging clinical entity. Issue 5 (4th May 2018) - Sahin, Ilyas; Mega, Anthony E.; Carneiro, Benedito A.
ABSTRACT: Androgen deprivation therapy remains the backbone of prostate cancer treatment given its pivotal role in the pathogenesis of prostate cancer. The growing knowledge of androgen receptor-independent (i.e. AR-null) prostate cancer cells, however, might advance the treatment paradigm of prostate cancer. Here, we examined the results of two recent studies, published in Cancer Cell by Bluemn and Shukla et al., and their impact in the future management of castration-resistant prostate cancer.